Effects of Aldosterone on Chemerin Expression And Secretion in 3T3-L1 Adipocytes - Ma, Junhua; Sun, Fei; Wang, Jingnan; Jiang, He; Lu, Jiancan; Wang, Xing; Zhang, Jichen; Shi, Chao; You, Wen; Li, Xiangqi; Zhu, Hongling; Gu, Mingjun (Experimental and Clinical Endocrinology & Diabetes, 2018)
Aldosterone plays a pivotal role in the pathogenesis of metabolic syndrome and cardiovascular disease; however, the underlying mechanisms have not been clarified. Chemerin has been characterized as an adipokine with crucial roles in obesity-associated disorders and cardiovascular homeostasis. The aim of the present study was to investigate the direct effects of aldosterone on chemerin expression and secretion in 3T3-L1 adipocytes and to identify the potential signalling pathways involved. Chemerin mRNA levels were measured using real-time PCR, whereas the levels of secreted chemerin in the culture media were determined using ELISA. Treatment with aldosterone induced time- and dose-dependent increases of chemerin gene expression and protein secretion, and effect that was mediated through the mineralocorticoid receptor. Signalling studies suggested that the NF-κB pathway is involved in aldosterone-induced chemerin expression. Taken together, our data demonstrate a direct interaction between aldosterone and chemerin in adipocytes, which may be an underlying mechanism linking aldosterone-associated metabolic abnormalities and cardiovascular disease.
Keywords: aldosterone; chemerin; 3T3-L1 adipocyte; metabolic syndrome; cardiovascular disease